Penerapan Model Project Based Learning Berbasis DGMATH untuk Meningkatkan Motivasi Belajar Siswa Sekolah Dasar - Prianggono, Agus; Yuniarti, Dwi Ariani; Pawening, Ari Setiyani (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2023)
Learning mathematics for students at the elementary school level is an important lesson to be concern. Learning model to use is a student centered learning model. DGMATH-based PBL is a student centered learning model and uses a DGMATH application that contain main subject is elementary arithmetic. The purpose of this study was to test the effectiveness of DGMATH-based PBL learning and measure how much influence student motivation had on learning outcomes from the implementation of DGMATH-based PBL learning. The method used is a quantitative method to test the effectiveness and regression test to learning motivation on DGMATH-based PBL learning with the subject of first grade students (1) SD Islam Insan Cendekia with a total of 60 students. The instruments used were learning tools, pre-test questions, post-test questions and student learning motivation questionnaires. The research results showed that in the completeness test the results were 82.83 in DGMATH-based PBL learning and in the average difference test with a sig value of 0.015 <0.05, which means that there is a significant difference in learning outcomes between the experimental class and the control class. So it can be concluded that DGMATH-based PBL learning has proven effective and learning motivation has an influence of 76% on learning outcomes.